Correlation of B-mode and Doppler Ultrasound Parameters of Kidney with Serum Creatinine Level in Chronic Kidney Disease Patients (Bangladesh Journal of Nuclear Medicine, 2024)
Abstract not availableBangladesh J. Nuclear Med. 27(1): 62-68, 2024